Kathryn the PE fairy - Meadows, Daisy (London : Orchard Books, 2016)
Kirsty and Rachel must help Kathryn the PE Fairy find her magical star badge. Jack Frost has stolen it, and PE lessons everywhere are a disaster! Can the girls get it back from him before the school inspector arrives?
5+.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction